La España de la Restauración, sobre la España de Cádiz. Un pequeño ejemplo: la zarzuela Cádiz - Banús Irusta, Enrique (Mercurio Peruano, 2020)
Las Cortes de Cádiz, which are as relevant to the processes of independence in America, also have a literary reception in Spain. At the time of the Restoration achieve great success zarzuela "Cádiz" master Federico Chueca, with the assistance of Alejandro Valverde. The popularity of Chueca joins the fact of being represented at the Apollo Theater, the "cathedral of small forms," as some have called it. It was, therefore, a zarzuela well known at the time. In it, the defense of Cadiz also, and the serene and humorous behavior of the population is presented as a paradigm of patriotism versus retrograde timid to reject the Constitution and they are cowards and adopt foreign ways. The vision of constitutional Cadiz and the Constitution itself is absolutely positive. The "March of Cadiz" included in the zarzuela was even about to become a national anthem. But the "disaster of 98" put paid to their popularity, being seen as an element that helped create enthusiasm for a war that could only lose.